An investigation into the transition of flow mechanism during fluidized dense-phase pneumatic conveying of fine powders. (2nd January 2016) - Mittal, A.; Mallick, S. S.; Wypych, P. W.
ABSTRACT: This paper presents results from an investigation into the changes in flow mechanism of pneumatic conveying of fine powders from dilute to fluidized dense-phase. Pressure fluctuations have been analyzed using power spectral density (PSD), Hilbert–Huang transformation (HHT), and wavelet transformation. Pressure fluctuations were obtained from conveying trials performed for two different types of powders, i.e., fly ash (median particle diameter: 30 µm; particle density: 2300 kg m −3 ; loose-poured bulk density: 700 kg m −3 ) and white powder (median particle diameter: 55 µm; particle density: 1600 kg m −3 ; loose-poured bulk density: 620 kg m −3 ). Power spectra obtained from PSD analysis, energy distribution of intrinsic mode functions obtained from HHT transformation, and wavelet scalogram show unique features related to the changing flow mechanism along the length of the pipeline. Results indicate variation from low frequency to higher frequency components in the signal, along the flow direction. Higher frequency components and wide range of frequencies in the signal obtained at pipeline exit might have resulted from increased level of interactions among solid particles, carrier gas, and pipe wall as compared to the power spectra with single dominant frequency (which corresponds to probable periodic dune formation) at pipeline entry region.